2015
DOI: 10.1007/s10620-015-3775-9
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Hepatitis B e Antigen Seroconversion in Chronic Hepatitis B Patients Treated with Entecavir or Tenofovir

Abstract: Introduction Loss of HBeAg and development of anti-HBe (seroconversion) is seen as a milestone and endpoint in the treatment of HBeAg-positive patients with chronic hepatitis B (CHB). Among patients treated with nucleos (t)ide analogs (NA), recurrent viremia is common after discontinuation of therapy. Entecavir (ETV) and tenofovir (TDF) are highly potent NA. The durability of virological response and HBeAg seroconversion in patients treated with these agents is not well studied. Methods We retrospectively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
1
26
0
2
Order By: Relevance
“…HBeAg seroconversion is closely associated with a sustained reduction in HBV DNA levels during therapy [21]. From this study, we showed that HBeAg seroconversion in NA-naïve and NA-experienced group was 27.8% (5/18) and 11.4% (4/35), respectively.…”
Section: Discussionmentioning
confidence: 66%
“…HBeAg seroconversion is closely associated with a sustained reduction in HBV DNA levels during therapy [21]. From this study, we showed that HBeAg seroconversion in NA-naïve and NA-experienced group was 27.8% (5/18) and 11.4% (4/35), respectively.…”
Section: Discussionmentioning
confidence: 66%
“…This indicates its ineffectiveness in clearing the cccDNA which is regarded as the hallmark of complete viral [5,7,16,19]. In such studies, a HBV DNA cutoff level of 20 to 2000 IU/mL was considered for stopping or restarting therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It became popular for its ease of use and generally high patient tolerance. Both short and long-term studies have shown its high efficiency in viral suppression [3,4], preventing liver disease progression in the form of cirrhosis, decompensation and hepatocellular carcinoma (HCC), but also its inefficiency in complete viral eradication [5][6][7]. Reports on its long-term use in Indian patients are scarce [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why aft er 3 years of viral suppression and substantial reduction in antigen exposure, the immune response has not re-established a state that will prevent the virus from replicating? Th is is a repetitive fi nding with other studies demonstrating that over 80% of the individuals with chronic HBV will relapse aft er stopping eff ective anti-HBV therapy ( 6,7 ). Part of the issue resides in the defi nition of response to therapy for chronic viral infection.…”
mentioning
confidence: 97%